American Society for Gastrointestinal Endoscopy guideline on gastrostomy feeding tubes: methodology and review of evidence - Divyanshoo Rai Kohli, MD; Natalie Cosgrove, MD; Wasif M. Abidi, MD, PhD; Jorge D. Machicado, MD, MPH; Madhav Desai, MD, MPH; Nauzer Forbes, MD, MSc; Neil B. Marya, MD; Nikhil R. Thiruvengadam, MD; Nirav C. Thosani, MD, MHA; Omeed Alipour, MD; Saowanee Ngamruengphong, MD; Sherif E. Elhanafi, MD; et al. (VideoGIE)
This article from the American Society for Gastrointestinal Endoscopy (ASGE) provides a full description of the methodology used to inform the final guidance outlined in the accompanying summary and recommendations article for strategies to manage endoscopically placed gastrostomy tubes. This article was developed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework and specifically addresses the utility of PEG versus interventional radiology–guided gastrostomy (IR-G), the need for withholding antiplatelet and anticoagulant medications, appropriate timing to initiate tube feedings, and appropriate selection of the gastrostomy technique in patients with malignant dysphagia. In patients needing enteral access, the ASGE suggests PEG as the preferred technique for initial gastrostomy over IR-G. The ASGE recommends that tube feeding can be safely started within 4 hours of the gastrostomy without the need for an intentional delay. The ASGE suggests that a PEG can be performed without the need to withhold antiplatelet medications. In patients on anticoagulants who need to undergo PEG placement, the ASGE suggests that the periprocedural management of anticoagulants should be based on a multidisciplinary discussion with the patient regarding the risk of bleeding versus cardiovascular adverse events. In patients with malignant dysphagia, either transoral “Pull” PEG or transcutaneous “Direct” PEG can be performed for initial enteral access.